Development Of A Multimedia-Based Independent Curriculum At Miss Hadirul Ulum - Rizky Fika Mulia; Ma’mun Hanif (Hikamatzu | Journal of Multidisciplinary, 2024)
MISS Hadirul Ulum Tasikrejo prepared a multimedia-based independent curriculum in response to changes in the development paradigm in the 2nd century. This curriculum will cover topics such as civilization-based welfare development, development capital as civilization, development capital as civilized human resources, and citizens as actors or producers. In the 21st-century learning paradigm shift, it is important to develop critical thinking in decision-making, formulate problems rather than just solve them, and seek knowledge from various sources. The aim of creating this curriculum is to understand the basis for curriculum development at MISS Hadirul Ulum, develop a multimedia-based independent curriculum structure, and ensure the relevance of independent curriculum development at the school. In the era of the fourth industrial revolution, special curriculum development is needed to support 21st century learning, including increasing the number of qualified teachers and adequate school infrastructure. By using the independent curriculum, it is hoped that students can develop critical thinking, problem-solving, communication, collaboration, creativity and discovery skills, as well as remain connected to their cultural values